Study of 150 kV Overhead Transmission Line Configuration Planning from Kambang Pesisir Selatan to Bengkulu City - Putra Winarta, Fadhel; Nasir Sonni, Muhammad; Eka Putra, R. Reski; Fahreza, Muhammad; Wahyudi, Ricky (Jurnal Teknik Elektro dan Komputasi (ELKOM), 2025)
The need for electricity is increasing due to the rise of human living standards, therefore, the provision and supply of electrical energy must be increased. To meet the increasing electricity demand, the construction of new generating plants or expanding of the transmission network is required. The most rational alternative to overcome the growing load in the Bengkulu Province is to construct a 150 kV transmission network from Kambang (Pesisir Selatan, West Sumatra Province) to Bengkulu (Bengkulu Province). Therefore, the Bengkulu region gets electricity supply from two areas, i.e.  the Central Sumatra Subsystem and the South Sumatra Jambi and Bengkulu Subsystem (S2JB). This 150 kV Transmission line span across of 396 kms that is matched with the government policy as an effort to enhance network reliability and adequacy of electricity supply in Sumatera region. This research aims to plan a transmission line from Kambang to Bengkulu City using load forecast based on the 2019-2028 RUPTL data of the Bengkulu area until year 2050. Calculation of 150 kV transmission line configuration is conducted by considering voltage regulation and load flow analysis by ETAP Software. The result of the Kambang – Bengkulu transmission line planning has capacity of 200 MW with receiving voltage of 150 kV, and frequency of 50 Hz, using 240 mm2 ACSR conductors with double circuit configuration and 2 bundle of conductor per circuit. The transmission line resistance is , the inductance of    and the capacitance of . The voltage regulation is 2,1% and the total line loss is 1.574 MW